2013
DOI: 10.1111/cts.12117
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Profiling in Patients with VCP‐Associated Disease

Abstract: Valosin Containing Protein (VCP) disease (also known as Inclusion Body Myopathy, Paget Disease of Bone and Frontotemporal Dementia (IBMPFD) syndrome) is caused by mutations in the gene encoding VCP classically affecting the muscle, bone and brain. Although the genetic cause has been identified, details regarding the pathogenesis of IBMPFD have not been fully determined. Muscle wasting observed in VCP disease is suggestive of cytokine imbalance. We hypothesized that dysfunctional protein homeostasis caused by V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…This is a crucial point as recent studies have demonstrated that skeletal muscle cells produce and release cytokines (myokines) that act in an autocrine, paracrine, and/or endocrine manner to modulate metabolic and inflammatory processes. For example, we recently found significant differences in circulating levels of cytokines (TNF-α and EGF) in patients with VCP disease versus healthy control groups [18]. However, the interactions between local NLRP3 expression/activation and these myokines production as well as the effects of these interactions on muscle function remain yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a crucial point as recent studies have demonstrated that skeletal muscle cells produce and release cytokines (myokines) that act in an autocrine, paracrine, and/or endocrine manner to modulate metabolic and inflammatory processes. For example, we recently found significant differences in circulating levels of cytokines (TNF-α and EGF) in patients with VCP disease versus healthy control groups [18]. However, the interactions between local NLRP3 expression/activation and these myokines production as well as the effects of these interactions on muscle function remain yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with VCP-associated disease exhibit progressive proximal limb girdle muscular weakness and eventually die prematurely, around 40–50 years of age, from progressive muscle weakness and cardiac/respiratory failure [14, 17]. The clinical inflammatory hallmark of VCP-associated diseases, together with our recent finding that muscle wasting in VCP disease is associated with an increase in inflammatory cytokines [18], prompted us to investigate the role of NLRP3 inflammasome in VCP-associated myopathy.…”
Section: Introductionmentioning
confidence: 99%
“…sIBM has proven abnormalities of proteasome metabolism and of autophagy/lysosomal-mitophagy [55,[69][70][71]. sIBM also has a lymphocytic "inflammatory" component, but the patients do not respond definitively to immunosuppression, suggesting a greater importance of the sIBM degenerative component, which remains untreatable (see Askanas et al chapter (77,78; also see Broccolini and Mirabella chapter, this issue). hIBM has vacuoles, and can have similar but fewer intra-myofiber cytoplasmic congophyllic amyloidic inclusions containing amyloid-B or phosphorylated-tau.…”
Section: Lysosomal Vacuolar Myopathiesmentioning
confidence: 99%
“…hIBM has vacuoles, and can have similar but fewer intra-myofiber cytoplasmic congophyllic amyloidic inclusions containing amyloid-B or phosphorylated-tau. hIBM is caused by an autosomal recessive mutation of the GNE or VCP gene [77,78].…”
Section: Lysosomal Vacuolar Myopathiesmentioning
confidence: 99%
“…Sjögren et al describe elevated TNFα levels in cerebrospinal fluid of pathologically uncharacterized FTD patients (7), suggesting that immune-modulatory therapies might prove beneficial in this condition. Additionally, in Paget Disease of Bone and Frontotemporal Dementia syndrome (another TDP-43 proteinopathy), Dec et al report elevated TNFa levels in plasma (8). In a remarkable coincidence, the growth factor progranulin (GRN), which is mutated in a rare familial form of FTD, directly binds to TNFa receptors as a TNFa antagonist (9, 10) (although this has been disputed by Chen et al (11)), is targeted by autoantibodies in various autoimmune disease (12), and modulates neuroinflammation and T-cell proliferation (13,14).…”
Section: Introductionmentioning
confidence: 99%